Upgrading existing dwellings as a housing strategy the Korean experience - Struyk, Raymond J. (1981)
Developing countries are confronted with the twin problems of producing adequate number of housing units to meet the increasing demand for dwelling units in the urban sectors, and of regulating the cost of housing to be within the reach of households in the lower ranges of the income distribution. Korea is one of such countries. Compounded by its government's policy of restricting the construction of core housing, upgrading the existing dwelling units as a means of improving the present housing condition of this country is imperative. The extent and determinants of upgrading existing dwelling units in the 31 urban centers of Korea are therefore analyzed to be able to develop housing strategies for developed countries.
Keywords: Public housing aspects -- Korea; Housing -- Korea -- Design and construction; Low-income housing